Naringin and temozolomide combination suppressed the growth of glioblastoma cells by promoting cell apoptosis: network pharmacology, in-vitro assays and metabolomics based study - Bisht, Priya; Prasad, Surendra Rajit; Choudhary, Khushboo; Pandey, Ruchi; Aishwarya, Dande; Aravind, Vulli; Ramalingam, Peraman; Velayutham, Ravichandiran; Kumar, Nitesh (Frontiers in Pharmacology, 2024)
Glioblastoma, which affects a large number of patients every year and has an average overall lifespan of around 14.6 months following diagnosis stands out as the most lethal primary invasive brain tumor. Currently, surgery, radiation, and chemotherapy with temozolomide (TMZ) are the three major clinical treatment approaches. However, the ability to treat patients effectively is usually limited by TMZ resistance. Naringin, a bioflavonoid with anti-cancer, antioxidant, metalchelating, and lipid-lowering effects, has emerged as a promising therapeutic option. To explore the targets and pathways of naringin in glioblastoma network pharmacology was used. The findings through the network pharmacology suggested that the key targets of naringin in the chemosensitization of glioblastoma would be Poly [ADP-ribose] polymerase 1 (PARP-1), O-6-Methylguanine-DNA Methyltransferase (MGMT), and caspases. The functional enrichment analysis revealed that these targets were significantly enriched in important pathways such as p53 signaling, apoptosis, and DNA sensing. Further, the results of the in-vitro study in U87-MG and T98-G glioblastoma cells demonstrated that TMZ and naringin together significantly reduced the percentage of viability and inhibited the DNA repair enzymes PARP-1 and MGMT, and PI3K/AKT which led to chemosensitization and, in turn, induced apoptosis, which was indicated by increased p53, caspase-3 expression and decreased Bcl2 expression. Additionally, a metabolomics study in T98-G glioblastoma cells using liquid chromatography high-resolution mass spectrometry (LC-HRMS) revealed downregulation of C8-Carnitine (-2.79), L-Hexanoylcarnitine (-4.46), DL-Carnitine (-2.46), Acetyl-L-carnitine (-3.12), Adenine (-1.3), Choline (-2.07), Propionylcarnitine (-1.69), Creatine (-1.33), Adenosine (-0.84), Spermine (-1.42), and upregulation of Palmitic Acid (+1.03) and Sphingosine (+0.89) in the naringin and TMZ treatment groups. In conclusion, it can be said that naringin in combination with TMZ chemosensitized TMZ antiglioma response and induced apoptosis in tumor cells.